Determining the Ideal Strategy in Facilitating Employment to Increase Public Investment in Melawi Regency using the SWOT Method - P. R. Benirobin; Muchlis Hamdi; Rossy Lambelanova; Reydonnizar Moenek (International Journal of Science and Society, 2020)
This research problem focuses on determining the local government's ideal strategy in facilitating employment in the Melawi Regency to increase public investment in the Melawi Regency. The research method is qualitative by conducting interviews, observation, and documentation. Researchers also conducted a SWOT analysis to find the right strategy in determining the strategy that the local government of Melawi Regency could undertake in facilitating employment to increase public investment in the Melawi Regency. The provincial government's role in facilitating the workforce to increase public investment in the Melawi Regency is not optimal due to factors of funds, infrastructure and facilities factors, information factors, and human resource factors. The study results explain that nine strategies can be done in facilitating employment to increase public investment in Melawi Regency.